Evaluation of Soil Physicochemical Properties across Distinct Land Use Systems at Bina Widya Campus, Universitas Riau - Chairina Fathin Rahmah,; Besri Nasrul,; Idwar, (Jurnal Online Pertanian Tropik, 2025)
Land use is one of the key factors influencing both the physical and chemical properties of soil, including characteristics such as soil color and texture. This study aimed to characterize the physicochemical properties and fertility criteria of soils under different land use types. Five land use categories were selected for investigation: shrubs, grasses, Eucalyptus sp., mixed plantations, and oil palm. Each land use type consisted of three replications. Soil sampling was conducted at five designated points per land use type, with samples collected from a depth of 0–30 cm, resulting in a total of 75 samples. The research was carried out over a three-month period from April to July 2022 using a land survey approach and purposive sampling technique. The observed parameters included soil color, texture, permeability, pH, total nitrogen (N), total phosphorus (P), total potassium (K), organic carbon (C), base saturation, and cation exchange capacity (CEC). The results revealed that the soil color was predominantly black (2.5Y 2/1), with a sandy loam texture. Soil permeability ranged from moderately fast to fast (6.33–23.68 cm·h⁻¹), while soil pH was acidic (4.75–5.11). Total nitrogen was categorized as low (0.11–0.18%), total phosphorus as very low (10.73–27.56 mg·100g⁻¹), and total potassium as very low to low (3.60–10.87 mg·100g⁻¹). Organic carbon content was low to moderate (1.49–2.45%), base saturation was very low (3.37–13.59%), and CEC was classified as very low to low (4.39–8.62 cmol(+)/kg).